Superselective transcatheter renal artery embolization for the treatment of hemorrhage from non-iatrogenic blunt renal trauma: report of 16 clinical cases - Rao D; Yu H; Zhu H; Yu K; Hu X; Xie L (Dove Medical Press, 2014)
Dapang Rao,1 Haifeng Yu,2 Haibo Zhu,2 Kaiyuan Yu,2 Xiao Hu,3 Liping Xie11Department of Urology, First Affiliated Hospital, Medical College, Zhejiang University, Hangzhou, People's Republic of China; 2Department of Urology, Second Affiliated Hospital of Wenzhou Medical College, Wenzhou, People’s Republic of China; 3Zhejiang University Medical College, Hangzhou, People’s Republic of ChinaObjective: To explore the therapeutic efficacy and outcome of superselective transcatheter renal artery embolization for the treatment of hemorrhage from non-iatrogenic blunt renal trauma (BRT).Methods: Sixteen patients who received superselective transcatheter renal artery embolization for non-iatrogenic BRT hemorrhage between January 2003 and December 2012 were reviewed retrospectively. Spring steel coils with gelatin sponge particles were used to embolize branches of the renal artery in 15 patients with injuries to the segmental or distal renal arteries; superselective internal iliac artery branch embolization was used to occlude hemorrhage from the branch of the renal artery in two patients with pelvic fracture complicated with internal iliac artery branch laceration; and balloon catheter occlusion was used to embolize the branch of the renal artery in one patient with renal artery trunk laceration.Results: Embolization was achieved successfully in a one-stop procedure in all cases. The patient who received balloon catheter occlusion for renal artery trunk laceration was transferred immediately to surgery for emergency nephrectomy. Another patient died of intracranial trauma 1 day after surgery, although macroscopic hematuria disappeared at the time. Macroscopic hematuria disappeared within 1 day after surgery in the other 14 patients. Follow-up visits at times ranging from 6 months to 9 years after the procedure showed normal renal function without evidence of complications in all surviving patients.Conclusion: Superselective transcatheter renal artery embolization is an effective minimally invasive therapy for the treatment of BRT hemorrhage.Keywords: blunt renal trauma, superselective cannulation, renal artery embolization